Ekphrasis l'écriture dans l'art : het schrift in de kunst : writing in art - Corà, Bruno 1942-; Salamé, Louma (La Fondation Boghossian, 2019)
The Boghossian Foundation is pleased to present the exhibition Ekphrasis, curated by Bruno Cora, director of the Burri Foundation in Italy. It brings together pieces from more than forty artists from around the world, whose styles are as varied as the media they use, but in whose works the use of language plays a key role. The definition of ekphrasis is a laudatory and constructed description of a work of art, real or imaginary, often designed on a model so as to achieve great evocative force. The first famous ekphrasis goes back to Greek Antiquity: this is the description Homer gives of Achilles' shield in the Iliad. The weapon was forged by Hephaestus so that "everyone should be amazed". If the rhetorical exercise of ekphrasis presents itself as an ancient practice, the genre has been used throughout the ages with remarkable continuity, with many famous writers exploring it. Conversely, many artists have also been inspired by reading ekphrases, like Botticelli, who produced a canvas based on a description from Antiquity. In fact, there is a great tradition of artists who have concerned themselves with both the visual arts and literature, poetry or politics, and for whom language is a constituent element of their work. The exhibition explores through the contemporary artists gathered here the issues raised and various preferred modes of the use of language in visual art. Exhibition: Boghossian Foundation - Villa Empain, Brussels, Belgium (24.10.2019 - 09.02.2020)
Publié à l'occasion de l'exposition "Ekphrasis, l'ecriture dans l'art". - Genaue Ausstellungsdaten ermittelt: 24 octobre 2019 au 9 février 2020, Fondation Boghossian - Villa Empain, Ixelles
Keywords: Skripturale Kunst; Ausstellungskatalog -- Fondation Boghossian -- 24.10.2019-09.02.2020 -- Brüssel; Bildband